THE NECESSITY, RELEVANCE, AND DEVELOPMENT PROSPECTS OF AN INTEGRATED APPROACH IN CHEMISTRY EDUCATION (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the necessity, relevance, and future prospects of implementing interdisciplinary integration principles in chemistry education. The essence of the integrative approach is reflected in the development of students’ complex thinking, logical analysis, and scientific as well as ecological reasoning. Research findings indicate that integrating chemistry lessons with physics, biology, mathematics, ecology, and technology significantly enhances students’ knowledge quality, motivation, and practical skills.The article also emphasizes the role of innovative methods such as the STEAM education approach, project-based learning, problem-based instruction, digital laboratories, and virtual simulations. As for the prospects of integrated education, the article substantiates the need to incorporate sustainable development concepts into the learning process, to improve teachers’ interdisciplinary competencies, and to strengthen preparation for international assessment systems.